Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.5826/dpc.1204a140
|View full text |Cite
|
Sign up to set email alerts
|

Serum Copper and Zinc levels among Iranian vitiligo patients

Abstract: Introduction: Vitiligo is a chronic skin disease, which its etiopathogenesis is not fully understood. Numerous studies have suggested that oxidative stress may play a role in the pathophysiology of vitiligo. There are controversial reports as to the changes of serum trace elements, copper and zinc levels in vitiligo patients. Objective: In this study, we evaluated the alterations in the level of serum Cu and Zn among a group of Iranian vitiligo patients. Methods: The levels of serum Cu and Zn were compared bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 35 publications
0
18
0
5
Order By: Relevance
“…In a case–control study on older adults with a sample size of more than 200, Khosdel et al 18 . found associations between Copper (Cu) and Zinc (Zn) levels and health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In a case–control study on older adults with a sample size of more than 200, Khosdel et al 18 . found associations between Copper (Cu) and Zinc (Zn) levels and health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Cu and Zn are essential micronutrients involved in several cellular processes and different diseases [ 20 , 21 ]. Previously, Malavolta et al depicted that the increase of Cu-Zn ratio was identified in several age-related chronic diseases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study evaluated changes in serum zinc levels in a group of Iranian patients with vitiligo. The results suggested that disturbances in serum zinc levels were associated with vitiligo and may have a crucial potential in the development of the disease in Iranian patients [42]. The main role of copper is that it promotes the production of melanin and participates in destroying free radicals by forming superoxide dismutase, thus providing physiological protection against oxidative stress [43].…”
Section: Antioxidant Therapy For Vitiligomentioning
confidence: 99%